Genipin-enhanced nacre-inspired montmorillonite-chitosan film with superior mechanical and UV-blocking properties. (29th September 2019) - Liang, Benliang; Shu, Yingqi; Wan, Pan; Zhao, Hewei; Dong, Shaohua; Hao, Weichang; Yin, Penggang
Abstract: Chitosan, as a functional material, has special characteristics: biocompatibility, biodegradability and sterilizable properties, suitable for use in many fields. However, the weak mechanical properties of this material limit its applications. Herein, inspired by the relationship between the hierarchical "brick-and-mortar" structure and excellent mechanical properties of natural nacre, monolayer montmorillonite sheet was selected as reinforcement nanoplatelet to construct nacre-mimetic layered structure with chitosan together. Genipin, a naturally occurring cross-linking agent, was introduced to further strengthen the nacre-mimetics through chemically cross-linking the amino group of chitosan matrix under alkaline condition. The effects of MMT content, GP crosslinking, and pH on the microstructure and interfacial interactions of the hybrid films were studied systematically. It is proved that the synergistic effect originating from hydrogen and covalent bonds improves the mechanical property of the bioinspired composites, generating a tensile strength of 226.3 MPa and a toughness of 5.1 MJ/m 3 . Meanwhile, the hybrid film has excellent UV-blocking ability (the transmittance is 10.0% at 365 nm) because the spontaneous reaction between GP and CS forms dark blue pigments. Such bioinspired hybrid films with improved mechanical properties and excellent UV-blocking ability has promising applications in aerospace, tissue regeneration, and construction.